Odonata Diversity and Ecological Thresholds in Protected Areas of the Brazilian Amazon - Sousa, Kenned Silva; Brito, Joás Silva; Cruz, Gabriel Martins; Bastos, Rafael Costa; Mendoza-Penagos, Cristian Camilo; Silva, Everton; Montag, Luciano; Oliveira-Junior, José Max Barbosa; Brejão, Gabriel [UNESP]; Casatti, Lilian [UNESP]; Michelan, Thaísa Sala; Juen, Leandro; et al. (Springer Nature, 2025)
The establishment of conservation units (CUs) aims to preserve biodiversity, yet these areas are under great anthropogenic pressure, particularly from logging, mining, and cattle ranching. Considering this context, our study assesses the importance of the protected area (National Park) and habitat integrity using the Habitat Integrity Index (HII) for conserving Odonata assemblages. Our hypothesis is that (1) the sites within the national park would have higher HII scores and greater Zygoptera diversity metrics (species diversity, abundance, proportions, and composition) compared to the scores of the sites outside the park; and (2) considering the habitat integrity of the streams, Anisoptera and Zygoptera serve as indicators, with the former associated with lower scores and the latter with higher scores. We sampled 25 streams (both within and outside) of the Jamanxim National Park, identifying 43 species of Odonata, including 16 Anisoptera and 27 Zygoptera. Streams outside the national park harbored the highest number of exclusive Anisoptera and Zygoptera species. Linear models revealed a significant negative correlation between habitat integrity and Anisoptera abundance only. Moreover, significant differences in Anisoptera abundance were observed between streams within and outside the national park, along with distinct heterogeneity in Anisoptera species composition. The decrease in Anisoptera abundance with increasing habitat integrity may be attributed to their preference for open areas for thermoregulation. Conversely, the positive response of Zygoptera species to habitat integrity underscores their reliance on more conserved environments, enhancing our understanding of their ecological requirements. These results reinforce the importance and efficiency of Odonata as a bioindicators of environmental quality and integrating the order into aquatic monitoring programs alongside the HII, provides a straightforward and objective measure of environmental disturbance.
Keywords: Aquatic environments; Biodiversity; Dragonflies; Environmental integrity; Freshwaters